Intranasal submucosal bevacizumab for epistaxis in hereditary hemorrhagic telangiectasia: A double‐blind, randomized, placebo‐controlled trial. Issue 6 (30th April 2014) - Riss, Dominik; Burian, Martin; Wolf, Axel; Kranebitter, Veronika; Kaider, Alexandra; Arnoldner, Christoph
Abstract Background The purpose of this study was to investigate the efficacy of bevacizumab ("Avastin") for the treatment of epistaxis in hereditary hemorrhagic telangiectasia (HHT). Methods In this double blind, placebo controlled trial, 15 adult patients with HHT with a minimum of 2 epistaxis episodes per week were randomized. A history of thromboembolic events or recent or planned surgery led to exclusion. Patients received a single intranasal submucosal injection (10 mL) of 100 mg bevacizumab or placebo. The primary outcome was the relative reduction of average daily epistaxis visual analog score (VAS). Results Average daily posttreatment VAS scores decreased by 27% in the bevacizumab group and by 3% in the placebo group (p = .57). The reduction in HHT epistaxis severity scores was ‐0.61 greater in the bevacizumab group compared to the placebo group (p = .34). Conclusion Results show a trend toward reduced epistaxis with bevacizumab. This further supports the use of bevacizumab in HHT. Clincial Trials. gov number: NCT01314274 © 2014 Wiley Periodicals, Inc. Head Neck 37: 783–787, 2015